Revolutionizing RKAS with Data: Achieving Efficient and Accountable School Financial Management - Putra, Wahyudi; Sujirman; Riyan; Harmi, Hendra; Ifnaldi; Ristianti, Dina Hajja (Al-Qalam Institue, 2025)
This study explores the use of data-driven planning to optimize the School Activity and Budget Plan (RKAS) at SMAIT Ma'had Rabbani, utilizing a strategy based on the education report card. The approach consists of three key steps: Identify, Reflect, and Fix. The results highlight that RKAS optimization can be effectively achieved by leveraging data from education report cards. Key issues identified included low learning quality and students' numeracy skills. Reflection revealed that suboptimal teaching methods (score 51.14) contributed to poor learning quality, while difficulties in data management and uncertainty (score 48.4) affected numeracy skills. In the Fix stage, a learning organization design was implemented, addressing intracurricular, co-curricular, and extracurricular activities, and mapping the needs for educator and staff competency development. The budgeting process includes five stages: budget calculation, identifying available funds, adjusting activities if the budget is insufficient, procurement through SIPLAH or other channels, and reporting on the Arkas platform. This research demonstrates that a data-driven approach enhances RKAS preparation, improving educational services and ensuring professional and accountable financial management.